2018
DOI: 10.1007/s12298-018-0561-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of nine cotton genes related to leaf senescence in Gossypium hirsutum L

Abstract: Leaf senescence is defined as a deterioration process that continues to the final developmental stage of leaf. This process is usually regulated by both external and internal factors. There are about 5356 senescence associated genes belonging to 44 plant species. A great number of these genes were identified in Arabidopsis. Leaf senescence can be regulated by many transcription factors. In this study, nine gene families were selected according to their expression levels during leaf senescence from our laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Besides, different TF families regulate leaf senescence in cotton. Elasad et al [190] reported nine cotton genes that increased their expression during leaf senescence, with CotAD_37422 as the only TF member of the GRF (ortholog to the AT4G37740.1 gene). Further analyses must be done to confirm the functionality of this TF in regulating leaf senescence [190].…”
Section: Main Tfs Associated With Leaf Senescence In Cropsmentioning
confidence: 99%
“…Besides, different TF families regulate leaf senescence in cotton. Elasad et al [190] reported nine cotton genes that increased their expression during leaf senescence, with CotAD_37422 as the only TF member of the GRF (ortholog to the AT4G37740.1 gene). Further analyses must be done to confirm the functionality of this TF in regulating leaf senescence [190].…”
Section: Main Tfs Associated With Leaf Senescence In Cropsmentioning
confidence: 99%
“…Gh_D06G0281 (DTX/MATE) overexpressing Arabidopsis improved tolerance to salt, drought, and cold stress with a high level of antioxidant enzyme production and significantly lower levels of oxidant ( Lu et al, 2019 ). Additionally, recent genome wide studies of PIN-FORMED ( PIN ), respiratory burst oxidase homolog ( Ghrboh ), Valine-glutamine ( VQ ) gene family, heat shock protein 20 (Hsp20), at-hook motif containing nuclear localized ( AHL ), leaf senescence, protein phosphatases (PP2C), 9-cisepoxycarotenoiddioxygenase (NCED), and Myo-inositol oxygenase (MIOX) have laid a foundation to predict the regulatory network of cotton genes in response to various abiotic stresses ( Ma et al, 2016 ; He et al, 2017 ; Elasad et al, 2018 ; Shazadee et al, 2019 ; Chen et al, 2020 ; Li Z. et al, 2020 ; Wang W. et al, 2020 ; Zhao et al, 2020 ; Li Q. et al, 2021 ). To gain a better understanding, we summarized the regulatory networks of cotton genes in response to salt and drought in this review ( Table 1 ).…”
Section: Genes Involved In Response To Salt and Drought Stressmentioning
confidence: 99%
“…Numerous studies have shown that NAC transcription factors are involved in the regulation of plant growth and development, resistance to stress, disease resistance, and hormone signaling [10,14]. Elasad et al discovered that the NAC transcription factor in cotton Gossypium positively regulates leaf senescence [15]. NAP is a member of the NAC family associated with senescence in Arabidopsis, and overexpression of the NAP gene resulted in early senescence, while the NAP mutant plants showed delayed senescence.…”
Section: Introductionmentioning
confidence: 99%